2003
DOI: 10.1002/ajim.10229
|View full text |Cite
|
Sign up to set email alerts
|

Lung function decrease in relation to pneumoconiosis and exposure to quartz‐containing dust in construction workers

Abstract: In quartz dust exposed construction workers obstructive and restrictive lung function loss was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
4
19
0
1
Order By: Relevance
“…For carpenters and tunnel workers prevalence of SCA was higher. These findings are similar to those reported by other investigators [Ulvestad et al, 2000;Tjoe-Nij et al, 2003]. In a cross-sectional study of 212 tunnel construction workers compared to outside and white-collar construction workers, 26% of tunnel workers reported chest tightness and wheeze [Ulvestad et al, 2000].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For carpenters and tunnel workers prevalence of SCA was higher. These findings are similar to those reported by other investigators [Ulvestad et al, 2000;Tjoe-Nij et al, 2003]. In a cross-sectional study of 212 tunnel construction workers compared to outside and white-collar construction workers, 26% of tunnel workers reported chest tightness and wheeze [Ulvestad et al, 2000].…”
Section: Discussionsupporting
confidence: 92%
“…Prevalence is high compared to our earlier study (4.6%) [Oliver et al, 2001] and similar to that of Tjoe-Nij et al [2003], who found that 10% of workers reported chronic cough with sputum. Twenty-nine percent of participants reported SOB.…”
Section: Discussionsupporting
confidence: 88%
“…Although some hazards, such as certain solvents in paints, may have been removed from occupations with multiple exposures, the potential for exposure to other hazards remains, for example, silica exposure in the construction industry, in which the number of employees is increasing. Studies in the Dutch construction industry suggested that over half of the full-shift respirable quartz dust measurements were above the Dutch Occupational Exposure Limit with exposure being highly variable from day to day and between jobs and tasks 77. In addition there will be considerable numbers of workers exposed at low levels and risk to some carcinogens that may contribute substantially to both high AFs and numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Cement masons are known to be significantly exposed to dust containing crystalline silica (quartz) (1) and, given ϳ500,000 such employees in the US (2), represent a sizable population at risk. Such workers are responsible for mixing, pouring, spreading, sanding, and grinding hard concrete.…”
Section: Introductionmentioning
confidence: 99%